Preoperative Low Lymphocyte-to-Monocyte Ratio Predicts Poor Clinical Outcomes for Patients with Urothelial Carcinoma of the Upper Urinary Tract - Zhang, Xin-Ke; Yang, Ping; Zhang, Zhi-Ling; Hu, Wan-Ming; Cao, Yun (Urology Journal, 2018)
Purpose: Urothelial carcinoma of the upper urinary tract (UUTUC) is a rare genitourinary tumor. Pre-operative lymphocyte-to-monocyte ratio (LMR) is associated with worse outcome in several malignancies. The aim of this study was to determine the prognostic value of pre-operative LMR in UUTUC. Materials and Methods: A historical cohort of 100 UUTUC patients was recruited from January 1990 to June 2011. The counts of peripheral lymphocyte and monocyte were retrieved, and the LMR was calculated by dividing lymphocyte count by monocyte count. Receiver operating characteristic curve (ROC) analysis, Log-rank test and Cox proportional hazards regression models were used for univariate and multivariate analyses to evaluate the associations of LMR with overall survival (OS) and disease-free survival (DFS). Result: Univariate analysis revealed that low level of LMR (? 3.0) was significantly associated with worse OS (P = .024) but not DFS (P = .993). Multivariate Cox proportional hazard analysis showed that low level of LMR was a significantly independent predictor for worse OS (hazard ratio = 0.366, 95% confident interval: 0.180-0.744). Based on the results of multivariate analysis, the rates of OS at 5 years developed by the prognostic model were as follows: low risk, 88.0%, intermediate risk, 44.0%, and high risk, 13.0%, respectively. Conclusion: The pre-operative LMR serves an independent prognostic biomarker in UUTUC. The prognostic model based on the LMR and pathologic factors can be available in selection of high risk patients for further aggressive therapy.